„Hasdeu: duhuri” de George Cornilă sau relectura unui enciclopedist - PILCHIN, Maria (BIBLIOPOLIS, 2025)
The author analyzes the literary biography „Hasdeu: spirits” by George Cornilă. The approach is one of critical analysis with arguments from the area of theories of reception regarding the reader of the literary text found in authorial synchrony (G. Cornilă), but in the historical and literary diachrony of the character (B.P. Hasdeu). The novelized writing allows to revisit and revalue a classical writer in the direction of a long tradition from the perspective of a current horizon of expectation. The receiver is transposed with the help of contemporary prose into the ambiance of the era and the historical context from which the character comes – an important writer and scholar. The concerns of reception are: the revaluation of the writing past, the literary portrayal of a personality from the 19th century, Bessarabian topographies, Chișinău imaginary, Hasdeu – the teacher and the librarian, the story of literature as a collective identity.